2012
DOI: 10.1099/ijs.0.031302-0
|View full text |Cite
|
Sign up to set email alerts
|

Postechiella marina gen. nov., sp. nov., isolated from seawater

Abstract: A Gram-staining-negative, strictly aerobic, non-motile, yellow-pigmented bacterium, designated strain M091T , was isolated from seawater at Damupo beach in Pohang, Republic of Korea, and investigated using a polyphasic taxonomic approach. The novel strain grew optimally at 25 6C, pH 7.0-8.0, and in the presence of 3 % (w/v) NaCl. In a phylogenetic analysis based on 16S rRNA gene sequences, strain M091 T formed a lineage within the family Flavobacteriaceae that was distinct from the most closely related genera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Strains and culture conditions P. marina M091 (KCTC 23537) was cultivated using previously described methods [16]. Pseudoalteromonas atlantica T6c (ATCC BAA-1087) was cultivated at 26°C in marine broth 2216 (Difco, Detroit, MI, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strains and culture conditions P. marina M091 (KCTC 23537) was cultivated using previously described methods [16]. Pseudoalteromonas atlantica T6c (ATCC BAA-1087) was cultivated at 26°C in marine broth 2216 (Difco, Detroit, MI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…For these purposes, microorganisms that hydrolyze and metabolize agar as a carbon and energy source were screened from seawater. Recently, we reported the characterization of one novel microorganism belonging to a new genus, Postechiella marina M091, which was isolated from a seawater sample obtained at Damupo beach in Pohang, Korea [16]. The phylogenetic analysis of the 16S rRNA of P. marina M091 showed that it belongs to the class Flavobacteria in the phylum Bacteroidetes.…”
Section: Introductionmentioning
confidence: 98%
“…It has been suggested that these bacteria could be used as one of the standards to test biosampling devices . E. Coli DH 5α is a motile, straight rod, that ranges in size from 1.1–1.5 × 2.0–6.0 µm . Motile organisms display a variety of shapes via expansion and contraction, as well as modes of locomotion, thereby allowing the organism to enter areas not accessible to nonmotile organisms.…”
Section: Methodsmentioning
confidence: 99%
“…28 E. Coli DH 5α is a motile, straight rod, that ranges in size from 1.1-1.5 × 2.0-6.0 μm. 30 Motile organisms display a variety of shapes via expansion and contraction, as well as modes of locomotion, thereby allowing the organism to enter areas not accessible to nonmotile organisms. In contrast, such characteristics may not be exhibited by nonmotile organisms.…”
Section: Bacterial Strains and Preparation Of The Bacterial Suspensionmentioning
confidence: 99%
“…P. marina M091, which was isolated from a seawater sample obtained at Damupo beach in Pohang, Korea, is a novel agar-degrading microorganism belonging to a new genus within the family Flavobacteriaceae [9].…”
Section: Previous Studies On L-angdh and L-angacimentioning
confidence: 99%